OPTIMALISASI PERAN PERPUSTAKAAN DALAM PENGEMBANGAN KOMUNIKASI ILMIAH DAN PENYEDIAAN E-RESOURCE UNTUK MENDUKUNG RISET DAN INOVASI PERGURUAN TINGGI - Rhoni Rodin (Ikatan Pustakawan Indonesia, 2018)
The Library’s College had a very urgent role in scholarly communication. Scholarly communication can run smoothly if the interest group as a chain functions properly. All components have an important role to create a healthy scholarly communication. The library as one of the interest groups has a strategic position in it. This paper emphasizes the optimalization of the role of the library’s college as one of the interest groups in the chain of scholarly communication. Various interest groups color the process of scholarly communication. The library functions as an information center that collects and disseminates various types of works both in scientific and non-categorized categories, including providing e-resources for researchers and academics in conducting research and innovation. In order for research and innovation in universities to run optimally, the library must communicate it to users (researchers / lecturers). Therefore, libraries need to make policies in terms of the types of e-resources that are available and served in libraries, access rights, network infrastructure and the internet to human resources in this case librarians. If all of the above elements are properly considered, the library can directly carry out its roles and functions properly as expected by a scholarly communication system.